The effects of electronic feedback on medical university students' writing performance - Noordin, Nooreen; Khojasteh, Laleh (Sciedu Press, 2021)
This study was designed to see whether electronic feedback positively affects medical students’ academic writing performance. Two groups of medical university students were randomly selected and participated in this study. In order to see whether the provision of electronic feedback for the compulsory academic writing course for medical students is effective, the researchers divided 50 medical students to the traditional (n=25) and intervention groups (n=25). Pre-test and post-test were conducted at the beginning and at the end of the semester. Electronic feedback was given to the medical students in the intervention group, while the medical students in the traditional group received the traditional pen and paper feedback. By comparing the scores of two written assignments at the beginning and the end of the semester, regarding the application of electronic feedback, the results showed that not only medical students’ overall writing performance improved after providing them electronic feedback, but every single writing component was also enhanced after the intervention. There was a significant difference in the post-test academic writing scores between the traditional and intervention groups (P < 0.001). This difference was not significant in our control group who was given pen-and-paper feedback. In terms of specific writing components, the most affected components in this approach were content followed by organization, language use, vocabulary, and sentence mechanics, respectively. Although this study focused on medical students’ academic writing ability and reported the effect of electronic feedback on medical students’ writing performance, electronic feedback can be equally beneficial for enhancing student-practitioners’ practical clinical skills.